Two-year stability and change among the honesty-humility, agreeableness, and conscientiousness scales of the HEXACO100 in an Australian cohort, aged 24–29 years - Dunlop, Patrick; Bharadwaj, Anupama; Parker, Sharon (Elsevier, 2021)
A surge in longitudinal personality research has yielded insights into how our personalities change over life stages. Very little of this research, however, has employed the HEXACO model of personality, and thus little is known about the life-course of, especially, the honesty-humility dimension, nor of the longitudinal psychometric properties of the HEXACO personality inventories. In this study, we investigate the stability and change over two years among three of the HEXACO dimensions (honesty-humility, agreeableness, and conscientiousness) using the HEXACO-100, in a sample of 214 members of an Australian cohort study (the Raine Study) in the later stage of early adulthood (ages 24–27 to ages 26–29). We found that the test-retest stability of the dimension and facet scales was generally high (0.80 for honesty-humility, 0.75 for agreeableness, and 0.74 for conscientiousness; mean for facets = 0.67), and that maturation in the sample was evidenced by increases in honesty-humility (d = 0.19), conscientiousness (d = 0.23), and to a lesser extent, agreeableness (d = 0.12) over the two years.